Native-Migrant Differences in Risk Attitudes - Holger Bonin; Amelie F. Constant; Konstantinos Tatsiramos; Klaus F. Zimmermann (Deutsches Institut für Wirtschaftsforschung (DIW), 2006)
This paper questions the perceived wisdom that migrants are more risk-loving than the native population. We employ a new large German survey of direct individual risk measures to find that first-generation migrants have lower risk attitudes than natives, which only equalize in the second generation.
Keywords: F22; D81; J31; J16; D1; J82; J15; J62; 330; Risk attitudes; ethnicity; native-migrant differences; gender differences; second-generation effects; Risikopräferenz; Migranten; Ureinwohner; Vergleich; Generationenbeziehungen; Deutschland